Quantitative and Qualitative Composition of Soil Organic Matter in Samples of Ice Complex from Central Yakutia, Eastern Siberia - Andrey Shepelev; Alexander Fedorov; Alexandra Cherepanova (Applied and Environmental Soil Science)
Investigation of organic carbon and nitrogen stock was conducted at depths greater than one meter in the ice complex in central part of Yakutia (Russia). Around 53% of the total organic carbon stock in the upper part of the ice complex is held in the active layer. The protective layer holds 31% and the permafrost layer holds 16%. The distribution of nitrogen over the elementary layers of the ice complex mirrors the percentages for organic carbon stocks given above. The total stock of biogenic elements in the ice complex investigated (0–250 cm) consists of 38.7 ± 0.2 kg/m2 of organic carbon and 2.13 ± 0.01 kg/m2 of nitrogen. The prevalent amount is carbon detritus, 40% of the total carbon content in the active layer. The share of labile carbon accounts 18%, that is 2 times less than carbon detritus. In the next two layers, the content of the components decreases and varies from 2% to 12%. The low labile organic matter content in the protective and permafrost layers indicates the development of the ice complex proceeded under conditions with poorly formed organic material.